Research shapes policy: but the dynamics are subtle - Foy, R; Locock, L; Purdy, S; O'Donnell, C; Gray, N; Doran, T; Davies, H (2013)
Major policy initiatives such as the Quality and Outcomes Framework (QOF) in the national contract for UK general practitioners might variably be informed by evidence at their inception, implementation and subsequent evolution. But what evidence gets admitted into these policy debates-and what is left out? Using QOF as an example, this article demonstrates what an analysis of the relationship between policy and the associated research can tell us about the underlying policy assumptions and about the role of evidence in policy debates. © 2013 Copyright CIPFA.